2019
DOI: 10.2118/191625-pa
|View full text |Cite
|
Sign up to set email alerts
|

Improved Understanding of Acid Wormholing in Carbonate Reservoirs through Laboratory Experiments and Field Measurements

Abstract: SummaryA comprehensive study on wormholing has been conducted to improve the understanding of matrix acidizing in carbonate reservoirs. This work is a continuation of the previous work by Furui et al. (2012a, 2012b). An analysis of additional experimental results, as well as field measurements, is provided to reinforce and extend the wormhole-penetration model and productivity benefits provided by Furui et al. (2012b).A series of small-block tests and one large-block test under geomechanical stresses have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…As a basic variant of acid in the study let's use acetic (ethanoic) acid [4,8,9] repeatedly described in the lite-rature at a concentration of 20 % in solution with a carrier. The main advantages of acetic acid are low reaction rate, which is important for high-temperature collectors, high stability, compatibility with basic solvents.…”
Section: Methods Of Researchmentioning
confidence: 99%
“…As a basic variant of acid in the study let's use acetic (ethanoic) acid [4,8,9] repeatedly described in the lite-rature at a concentration of 20 % in solution with a carrier. The main advantages of acetic acid are low reaction rate, which is important for high-temperature collectors, high stability, compatibility with basic solvents.…”
Section: Methods Of Researchmentioning
confidence: 99%
“…They observed that as a hydraulic fracture approaches a natural fracture, the natural fracture simultaneously experiences compressive (the region of the natural fracture shadowed by the hydraulic fracture) and tensile (the region of the natural fracture in front of the hydraulic fracture) stresses which can further result in the partial failure of the natural fracture and in both the crossing and the intersection of the hydraulic fracture with the natural fracture [14]. The presence of natural fractures in carbonate reservoirs, which are candidates for acid fracturing, tend to reduce the productivity of acid fractured wells, because the natural fractures increase leakoff, which causes the main hydraulic fracture to be shorter [15,[37][38][39][40][41]. Alsulaiman et al (2020) developed a model to explain acid (reactive fluid system) distribution in hydraulic and intersecting natural fractures and then used it to explain the complex interactions of acid fractures in naturally fractured carbonate formations and to optimize acid fracture design parameters.…”
Section: Relationship Between Hydraulic Fractures and Natural Fracturesmentioning
confidence: 99%